Perancangan Sistem Dinding Penahan Banjir Otomatis Berbasis Internet of Things (IoT) Menggunakan ESP32 - Farhan Fadillah Panjaitan; Mhd Basri (Medan Resource Center, 2026)
Floods frequently cause significant environmental and infrastructural damage, while conventional monitoring systems often experience delayed responses. This study aims to design an automatic flood barrier system based on the Internet of Things using Espressif Systems 32 as the primary microcontroller. The research investigates how real-time monitoring and automated control can improve flood mitigation effectiveness. The system employs a load cell sensor integrated with the HX711 module to detect water pressure as an indicator of flood risk. Data are processed by the microcontroller and classified into normal, alert, and danger conditions. A linear actuator automatically activates the flood barrier when critical thresholds are reached. The system also transmits data via Wi-Fi using the Hypertext Transfer Protocol to a web-based monitoring dashboard for real-time observation. The results indicate that the system can accurately detect water pressure changes, activate the actuator automatically, and deliver monitoring data efficiently in real time. The study concludes that the proposed system offers an effective and responsive solution for automated flood mitigation.